Differences in epitope‐specific antibodies to pertussis toxin after infection and acellular vaccinations. Issue 8 (2nd August 2020) - Knuutila, Aapo; Dalby, Tine; Barkoff, Alex‐Mikael; Jørgensen, Charlotte Sværke; Fuursted, Kurt; Mertsola, Jussi; Markey, Kevin; He, Qiushui
Abstract: Objectives: Pertussis toxin (PT) is a component of all acellular pertussis vaccines. PT must be detoxified to be included in acellular vaccines, which results in conformational changes in the functional epitopes of PTs. Therefore, induced epitope‐specific antibodies to PT may vary after vaccinations or natural infections, and this information could reveal biomarkers implicated for protection and successful immunisation. Methods: Pertussis toxin epitope‐specific antibodies in sera from 152 vaccinated children and 72 serologically confirmed patients were tested with a blocking ELISA, based on monoclonal antibodies that target protective PT epitopes. Results: All study groups induced considerable antibody titres to subunit 1 (S1). Of interest, S3 7E10‐specific antibodies were present in patients, but not after vaccinations ( P < 0.001). The impact of glutaraldehyde treatment of PT was visible on epitope 1D7 (S1), whereas epitopes 1B7 (S1) and 10D (S1) were more preserved. Antibodies to these epitopes were higher after three primary vaccine doses than after a single booster dose. Conclusion: The high amount of 7E10‐specific antibodies in patients suggests this epitope might be functionally relevant in protection. The overall characteristics of epitope‐specific antibodies are influenced by infection or vaccination background, by the used detoxification method of PT and by the amount of the toxin used in immunisation. Abstract : A blocking ELISA was developed for measuring different epitope‐specific antibodies to pertussis toxin from human sera. Although infection and acellular vaccinations induced considerable antibodies to subunit 1, antibodies to one epitope of subunit 3 were present mainly after infection.